Examining the Influences of the Mathematics Teachers’ Pedagogical Content Knowledge on Learning Algebra in Grade Six - Rupasinghe, D.D.; Amarasinghe, A.K.; Vitharana, P.R.K.A. (University of Jaffna, 2022)
This mixed method study findings indicate that the pedagogical content knowledge (PCK) of the teachers is an influencing factor of learning algebra in grade six in Sri Lankan schools. Reliable and validated two questionnaires followed by 24 of eight mathematics teachers’ classroom observations and post- lesson interviews were administered for collecting data in the explanatory sequential mixed methods research design. Field notes, lesson video recordings and the interview data were triangulated in terms of the reliability of the qualitative data while the two questionnaires were piloted and designed by Delphi method before collecting quantitative data. The Cronbach’s alpha of the questionnaire-2 was 7.59. SPSS statistical software was used in the first phase while the reflexive thematic analysis method was used in the second phase of the data analysis process. The study results of the first phase indicate that the mathematics teachers’ PCK in teaching algebra is at a medium level and not satisfactory. Teachers’ PCK in algebra was found to be multi-functional, indicating no positive relationship with academic qualification, professional qualification and professional experiences. Further analysis showed that there was no correlation between the PCK and the PCK knowledge dimensions, declarative, procedural and conditional knowledge. Qualitative study results revealed that the mathematics teachers’ PCK is low, in building algebraic concepts in the students’ mind, addressing the students’ algebraic misconceptions and understanding of students’ algebraic thinking. Finally, learning algebra in algebraic symbols, variables and algebraic expressions were observed and found to be less effective. Therefore, content knowledge and pedagogical knowledge based professional teacher development programs are recommended for enhancing the students’ learning algebra in the classrooms.
Keywords: Algebra; Algebraic Misconceptions; Algebraic Thinking; Concept Building; Pedagogical Content Knowledge